THE EFFECT OF UTILIZING IE KULOH SIRA, IE ASAM SUNTI, AND CORNELA ON THE CHARACTERISTICS OF SILK TOFU - Salmyah, S; TA, Cut Fatmawati; Haziri, Ahmad Abrar; Rahmawati, Cut Aja (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACTSilken tofu is a type of tofu that has a soft and compact texture. Ie kuloh sira and ie acid sunti can be used as coagulants. The lack of this coagulant results in a tofu texture that is not compact. Therefore, cornstarch is added to the making of silken tofu to improve the quality of the resulting silken tofu texture. This study aims to determine the effect of the type and concentration of coagulant and cornstarch concentration on the characteristics of silken tofu and the shelf life of silken tofu. This research method uses the Response Surface Method (RSM) and the organoleptic method. Coagulant concentration (0.5%, 1%, 1.5%, 2%, 2.5%) and cornstarch concentration (5%, 10%, 15%, 20%, 25%). The results obtained for silken tofu with coagulant ie kuloh sira and cornstarch obtained the optimal value, namely at concentrations of ie kuloh sira 2% and cornstarch 10% producing a protein content of 8.45%, texture 4.5 mm/sec. The concentration of ie kuloh sira and cornstarch did not affect the color and aroma of silken tofu, but it did affect the taste of silken tofu. Meanwhile, silk tofu with coagulant ie acid sunti and cornstarch obtained the optimal value, namely at a concentration of 1.5% ie acid sunti and 15% cornstarch producing a protein content of 7.57%, texture 4 mm/sec. The concentration of ie acid sunti and cornstarch has an effect on the color of silken tofu, but has no effect on the aroma and taste of silken tofu. The shelf life of silken tofu with coagulant ie kuloh sira and ie asam sunti only lasted 15 hours at room temperature. Meanwhile, those stored in the refrigerator can last for 3 days with a coagulant ie kuloh sira and 5 days with a coagulant ie acid sunti. Keywords: silken tofu, namely kuloh sira, namely sunti acid, cornstarch, RSM